Disparities in the Human Development Index and Their Implications for Human Capital Inequality in West Java - Eny Nuryani Resmiati; Iwan Ardiansyah (PT. Riset Press International, 2026)
The disparity in the Human Development Index (HDI) across regions in West Java Province reflects inequalities in human resource quality, with significant implications for regional development gaps. This study aims to analyse the patterns of HDI disparity across districts and cities in West Java over the period 2020–2024 and to examine its implications for human resource inequality, employing a descriptive quantitative approach using secondary data from the West Java Provincial Statistics Agency (BPS). The analytical techniques applied include descriptive statistics, the Williamson Index to measure the degree of disparity, and component analysis of HDI encompassing Life Expectancy at Birth (LEB), Expected Years of Schooling (EYS), Mean Years of Schooling (MYS), and per capita real expenditure. The findings reveal significant HDI disparities ranging from 68.66 (Cianjur Regency) to 82.14 (Bekasi City) in 2024, representing a gap of 13.48 points. Urban areas exhibit substantially higher HDI scores compared to regencies, with the educational dimension—particularly Mean Years of Schooling—emerging as the primary contributor to the disparity, with a coefficient of variation of 14.23%. These disparities have broad implications for human resource quality inequality, as evidenced by differences in productivity, labour competitiveness, and access to economic opportunities across regions. This study contributes to regional human development studies by emphasising the role of educational inequality in shaping HDI disparities and strengthening the application of the Williamson Index in analysing human capital inequality. The study recommends affirmative policy interventions to accelerate human development in lagging regions through improved access to education, healthcare services, and equitable infrastructure development.